CONCEPT CARTOON- A CONSTRUCTIVIST STRATEGY TO ENHANCE POSITIVE ATTITUDE TOWARDS SCIENCE IN MALAYSIA: AN ANCOVA REPEATED MEASURES APPROACH - Norfarah, N.; Mohd Ali, S.; Chong, L.Y. (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This research aims to examine the effectiveness of the Concept Cartoon approach in enhancing students’ attitude towards science. A Quasi-experimental research design was employed involving 60 primary school students from two schools in Penang, Malaysia. Data was analyzed using One-Way-ANCOVA approach. Thirty students from school A were assigned as a control group and science subject was taught employing conventional teaching approach, and thirty students from school B were assigned as the experimental group and were taught employing concept cartoon approach. The results showed a significant difference between post-test mean scores of the Attitude towards Science in the experimental group that was taught using concept cartoon teaching approach as compared to the control group that was taught using the conventional teaching approach. The experiment supports that teaching science employing concept cartoon approach enhanced students’ attitude towards science in the case of Malaysian schools students.